Translational and rotational localization errors in cone-beam CT based image-guided lung stereotactic radiotherapy. Issue 7 (July 2016) - Garibaldi, Cristina; Piperno, Gaia; Ferrari, Annamaria; Surgo, Alessia; Muto, Matteo; Ronchi, Sara; Bazani, Alessia; Pansini, Floriana; Cremonesi, Marta; Jereczek-Fossa, Barbara Alicja; Orecchia, Roberto
Highlights: We determined localization and residual errors for 57 lung SBRT using CBCT. Translational and rotational errors were detected using ITV/CBCT matching technique. The automatic 6D correction with the robotic couch increased localization accuracy. 5 mm safety margin to the ITV resulted adequate using the automatic 6D correction. Abstract: Purpose: Accurate localization is crucial in delivering safe and effective stereotactic body radiation therapy (SBRT). The aim of this study was to analyse the accuracy of image-guidance using the cone-beam computed tomography (CBCT) of the VERO system in 57 patients treated for lung SBRT and to calculate the treatment margins. Materials and methods: The internal target volume (ITV) was obtained by contouring the tumor on maximum and mean intensity projection CT images reconstructed from a respiration correlated 4D-CT. Translational and rotational tumor localization errors were identified by comparing the manual registration of the ITV to the motion-blurred tumor on the CBCT and they were corrected by means of the robotic couch and the ring rotation. A verification CBCT was acquired after correction in order to evaluate residual errors. Results: The mean 3D vector at initial set-up was 6.6 ± 2.3 mm, which was significantly reduced to 1.6 ± 0.8 mm after 6D automatic correction. 94% of the rotational errors were within 3°. The PTV margins used to compensate for residual tumor localization errors were 3.1, 3.5 and 3.3 mm in the LR, SI and AP directions, respectively. Conclusions: On-line image guidance with the ITV–CBCT matching technique and automatic 6D correction of the VERO system allowed a very accurate tumor localization in lung SBRT.